Communication—Tunable Epsilon-Negative Property of Nickel/Copper Calcium Titanate Cermets. (27th November 2020) - Ding, Baogang; Lin, Jiamin; Wan, Feng; Qu, Yunpeng; Wu, Jiada; Sun, Kai; Fan, Runhua
Abstract : Nickel/copper calcium titanate (Ni/CCTO) cermets with variated Ni content were prepared. The abrupt shift of ac conductivity, reactance and complex permittivity occurred in composites. Epsilon-negative property is an intrinsically physical performance of inductive character which was explained by low-frequency plasmonic state of Ni networks. Negative value of real permittivity in metacomposites reached 10 9 and was tuned by adjusting the concentration of free carriers in Ni networks. The epsilon-negative materials are accompanied by strongly dielectric loss and high reactance value. This work expands the applying scope of CCTO into metacomposites and meanwhile facilitates to clarify the regulation mechanism of epsilon-negative.